STRATEGI PENGEMBANGAN USAHA ‘DIKA BAN KALASAN’ DENGAN PENDEKATAN MATRIKS SPACE (PENDEKATAN STUDI KASUS) - Ferdika Adhi Pradana; Reza Widhar Pahlevi (Bajang Institute, 2022)
This study aims to analyze the internal and external factors of the motorcycle workshop ‘Dika Ban Kalasan’ using a space matrix approach. The type of research used is descriptive with a qualitative approach. The type of data used is qualitative data. Sources of data used are primary data and secondary data. The data collection procedure used interviews and documentation. The data analysis used is descriptive method, while the data validity test uses source triangulation. The analysis technique uses the Space Matrix approach which is used to evaluate and sharpen the strategic position by providing a rating or weighting for each factor. The results of this study indicate that the motorcycle repair shop ‘Dika Ban Kalasan’ is in quadrant I. On the Cartesian Space Matrix chart where strength is greater than weakness, and opportunity is greater than threats. Based on the SWOT analysis, the strategy that can be applied to the motorcycle repair shop ‘Dika Ban Kalasan’ is a strategy that supports being aggressive. The strategy that supports the aggressive policy at the motorcycle repair shop